Using a Sam-based model to measure the distributional impacts of government policies - Santos, Susana (2009)
A Social Accounting Matrix (SAM) will be proposed as a working instrument for studying the (macro-)impacts of government policy on the distribution of income. A numerical version of the SAM, constructed from the System of National Accounts (SNA), will serve as the basis for the construction of an algebraic version of the same matrix for Portugal. To this end, a computable (numerically solvable) general (economy-wide) equilibrium (macroeconomic balance) approach will be adopted. A SAM-based model will be constructed, in which each cell is defined with a linear equation or system of equations, whose components are all the known and quantified transactions of the SNA, using parameters deduced from the numerical SAM that served as the basis for this model. A scenario will be defined and analysed from an experiment carried out in relation to the distributional impact of a reduction in the direct tax rate paid by households.